Studies in natural products chemistry. - Rahman, Atta-ur- 1942- (Elsevier, 2013)
Natural products present in the plant and animal kingdom offer a huge diversity of chemical structures which are the result of biosynthetic processes that have been modulated over the millennia through genetic effects. With the rapid developments in spectroscopic techniques and accompanying advances in high-throughput screening techniques, it has become possible to isolate, and then determine the structures and biological activity of natural products rapidly, thus opening up exciting new opportunities in the field of new drug development to the pharmaceutical industry. The series covers all of the above as well as the synthesis or testing and recording of the medicinal properties of natural products. Describes the chemistry of bioactive natural products Contains contributions by leading authorities in the field A valuable source for researchers in natural product and medicinal chemistry.